El diseño de una estrategia de evaluación de los aprendizajes de niños y niñas con características diversas: un aporte para transformar el aula - Chávez Rincón, Berenice (2020)
This article addresses the design of an evaluation strategy for the learning of children with diverse characteristics, based on the implementation of the Universal Learning Design (ULD) and from the qualitative methodology of an evaluative-projective type. I propose to present the findings and conclusions from the four categories of analysis: educational evaluation, evaluation of learning, learning strategies, population with diverse characteristics and the methodological approach proposed by the ULD. The information collected showed that for teachers, there is neither clarity nor standardization in the instruments used to evaluate students; the use of summative but non-training type assessment predominates. In the teaching-learning process, it is evident that, although there is class planning, the flexible criteria and procedures of educational evaluation from an inclusive perspective are not reflected. It was concluded that the ULD can be a key tool to make use of different pedagogical strategies and to make the curriculum more flexible, and the design of a methodological evaluation strategy can universalize classroom practice and lower learning barriers for inclusive population.   DOI: https://doi.org/10.31876/sl.v4i1.52